2018
DOI: 10.3748/wjg.v24.i23.2482
|View full text |Cite
|
Sign up to set email alerts
|

Association of twelve polymorphisms in three onco-lncRNA genes with hepatocellular cancer risk and prognosis: A case-control study

Abstract: AIMTo evaluate the association of 12 tag single nucleotide polymorphisms (tagSNPs) in three onco-long non-coding RNA (lncRNA) genes (HOTTIP, CCAT2, MALAT1) with the risk and prognosis of hepatocellular cancer (HCC).METHODSTwelve tagSNPs covering the three onco-lncRNAs were genotyped by the KASP method in a total of 1338 samples, including 521 HCC patients and frequency-matched 817 controls. The samples were obtained from an unrelated Chinese population at the First Hospital of China Medical University from 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 37 publications
1
40
1
Order By: Relevance
“…In addition, rs591291 highlighted better prognosis in female and HBV negative subgroups. The association between MALAT1 haplotype (rs4102217-rs591291-rs11227209-rs619586) and HCC risk were not found [25]. In contrast to HCC, we found that A-C-A-G (rs600231-rs1194338-rs4102217-rs591291) haplotype had a 1.3-fold IS risk (Table 4) although SNPs (rs600231, rs4102217, rs591291) did not correlate with IS susceptibility.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition, rs591291 highlighted better prognosis in female and HBV negative subgroups. The association between MALAT1 haplotype (rs4102217-rs591291-rs11227209-rs619586) and HCC risk were not found [25]. In contrast to HCC, we found that A-C-A-G (rs600231-rs1194338-rs4102217-rs591291) haplotype had a 1.3-fold IS risk (Table 4) although SNPs (rs600231, rs4102217, rs591291) did not correlate with IS susceptibility.…”
Section: Discussionmentioning
confidence: 64%
“…It was reported that genetic variants in the promoter region can affect disease occurrence by involving in transcription efficiency, genetic stability and function [23,24]. At the same time, studies also showed that polymorphisms in MALAT1 affect susceptibility and progression of some diseases [25][26][27], but the impacts on IS have rarely been explored. To date, no study was conducted for the SNPs (rs600231, rs1194338, rs591291 and rs4102217) in promoter of MALAT1 with IS risk.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the rs2240183 C allele of lncRNA TUG1 was associated with a higher risk of IS possibly by binding to GATA-1 and elevating TUG1 levels [20], the ANRIL rs2383207 increased the risk of IS by 1.52-fold under the recessive mode [21], the rs217727 TT and rs4929984 AA in the H19 increase the risk of IS, with adjusted OR 4.288, 3.020, respectively [22]. Those provide a new perspective on the genetic mechanism of IS.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al indicated rs4102217 and rs591291 SNPs were not associated with RA susceptibility [35]. Studies of association with HCC have shown rs4102217 had a 1.32-fold risk in the dominant model, and rs591291 highlighted better prognosis in female and HBV negative subgroups, but association between MALAT1 haplotype (rs4102217-rs591291-rs11227209-rs619586) and HCC risk were not found [22]. In our study, we found that A-C-A-G (rs600231-rs1194338-rs4102217-rs591291) haplotype had a 1.3-fold IS risk (Table 4) although SNPs (rs600231, rs4102217, rs591291) did not correlate with IS susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation